The concept of Tritangtu at Tarawangsa music performance in Pasir Biru Village, Rancakalong, Sumedang - Ferawati, Sri Rahayu; Setiawan, Aris (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2023)
This study aims to reveal the aesthetics of the concept of Tritangtu (the trinity) in the Tarawangsa music performance in Kampung Pasir Biru, Rancakalong, Sumedang. Tarawangsa is a ritual ceremony related to religious magic to honor Keursa Nyai (goddess of fertility). The music in this ritual is not just an accompaniment or ritual compliment but even deeper shows a strong connection with the concept of Tritangtu, namely the world of heaven, the human world, and the underworld. This study uses the ethnographic method, by performing an in-depth recording of the event. The recording is to find out in more detail why Tarawangsa music is played, in what context, and how do people believe in it. In addition, the concept of Tritangtu, belief in three main elements (metacosm, microcosm, and macrocosm) shows a thought of the Rancakalong people about the balance of human life with God and nature. The study results show that the cultural customs of the Pasirbiru community, in general, indicate how this balance is maintained. They believe there will be a significant impact if one of the Tritangtu elements is not fulfilled, and Tarawangsa's music is an essential element in this effort.